Patient and Clinician Perspectives of New and Return Ambulatory Teleneurology Visits. Issue 6 (December 2021) - Kling, Samantha M.R.; Falco-Walter, Jessica J.; Saliba-Gustafsson, Erika A.; Garvert, Donn W.; Brown-Johnson, Cati G.; Miller-Kuhlmann, Rebecca; Shaw, Jonathan G.; Asch, Steven M.; Yang, Laurice; Gold, Carl A.; Winget, Marcy
Abstract : Background and Objectives: To evaluate the adoption and perceived utility of video visits for new and return patient encounters in ambulatory neurology subspecialties. Methods: Video visits were launched in an academic, multi-subspecialty, ambulatory neurology clinic in March 2020. Adoption of video visits for new and return patient visits was assessed using clinician-level scheduling data from March 22 to May 16, 2020. Perceived utility of video visits was explored via a clinician survey and semistructured interviews with clinicians and patients/caregivers. Findings were compared across 5 subspecialties and 2 visit types (new vs return). Results: Video visits were adopted rapidly; all clinicians (n = 65) integrated video visits into their workflow within the first 6 weeks, and 92% of visits were conducted via video, although this varied by subspecialty. Utility of video visits was higher for return than new patient visits, as indicated by surveyed (n = 48) and interviewed clinicians (n = 30), aligning with adoption patterns. Compared with in-person visits, clinicians believed that it was easier to achieve a similar physical examination, patient-clinician rapport, and perceived quality of care over video for return rather than new patient visits. Of the 25 patients/caregivers interviewed, most were satisfied with the care provided via video, regardless of visit type, with the main limitation being the physical examination. Discussion: Teleneurology was robustly adopted for both new and return ambulatory neurology patients during the COVID-19 pandemic. Return patient visits were preferred over new patient visits, but both were feasible. These results provide a foundation for developing targeted guidelines for sustaining teleneurology in ambulatory care.